(untitled) (The Pakistan Development Review, 2002)
Women’s involvement in domestic decision-making is recognized as a distinct aspect of her autonomy that has its implications for reproductive behaviour. Using data from the Pakistan Fertility and Family Planning Survey 1996-97, this study examines the extent of Pakistani women’s participation in household decision-making relative to their husbands and other family members, and determines its effects on the demand for children and higher contraceptive use in both urban and rural settings. The findings reveal that women’s decision-making authority is clearly related to the context in which they live as urban women have an almost equal say in household matters, as their husbands, whereas most rural women report that their husbands and other family members have a predominant role in household decisions with regard to seeking medical treatment for a sick child or to make purchases of household items. The results also indicate that women with greater freedom to go outside home alone are also more likely to participate in domestic decisions, and the linkage is stronger for rural than urban women. The multivariate analysis reveals that the effect of decision-making variables on measures of reproductive behaviour is strongly conditioned by socio-economic and demographic factors, implying that measures of women empowerment give only a partial explanation of women’s likelihood to desire fewer children and increase contraceptive use. The results in all suggest that Pakistani women’s enhanced role in household decision-making has its effects relevant to achieving gender equality and fertility reduction outcomes - the goals that are central to population and development policy.